Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s00414-019-02147-5
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation using canine pulp volumes in adults: a CBCT image analysis

Abstract: Secondary dentine deposition is responsible for the decrease in the volume of the pulp cavity with age. Therefore, the volume of the pulp cavity can be considered as a predictor for estimating age. The aims of this study were to investigate the relationship strength between canine pulp volumes and chronological age from homogenous (approximately equal numbers of individuals in each age range) age distribution and to assess the effect of sex as predictor in age estimation. This study was performed on 719 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 39 publications
(78 reference statements)
3
57
1
12
Order By: Relevance
“…In the recent past, increasing numbers of publications have reported an approach to calculate the actual volume of the dental pulp or a quotient of the volume of the hard tooth substance and the pulp [21][22][23][24][25][26]. These methods are based on the cone-beam CT (CBCT) for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, increasing numbers of publications have reported an approach to calculate the actual volume of the dental pulp or a quotient of the volume of the hard tooth substance and the pulp [21][22][23][24][25][26]. These methods are based on the cone-beam CT (CBCT) for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a significant negative correlation between the ratio of canine's pulp/tooth area and age in Egyptians was reported in previous studies (Afify et al 2019;Salemi et al 2020). Conversely, Kazmi et al (2019) reported that each of the maxillary and mandible canine pulp volumes had non-linear correlation with chronological age in the Pakistani population. They observed consistent decrease of the pulp volume as the individual's age increases; however, the rate of change in the pulp volume was not fixed among different early, middle, and old ages.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, various studies revealed no significant differences between both sexes in the canine teeth of Egyptians (Afify et al 2014;Afify et al 2019;Salemi et al 2020), Tunisians (Nemsi et al 2017), Indians (Saxena 2011), and Portuguese (Cameriere et al 2009). Conversely, a study performed on 717 CBCT images of Pakistani origin subjects revealed significant differences of the canine's pulp volumes between males and females (Kazmi et al 2019). It seems that sex differences of the teeth are related to the selected teeth and measurements as well as the applied techniques, methods, and the studied population (Marroquin et al 2017).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations